2013
DOI: 10.1002/swe.20092
|View full text |Cite
|
Sign up to set email alerts
|

A survey of customers of space weather information

Abstract: [1] We present an analysis of the users of space weather information based on 2783 responses to an online survey among subscribers of NOAA's Space Weather Prediction Center e-mail services. The survey requested information focused on the three NOAA space weather scales: geomagnetic storms, solar radiation storms, and radio blackouts. Space weather information is most commonly obtained for reasons of human safety and continuity or reliability of operations. The information is primarily used for situational awar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The official US space-weather forecast center (the Space Weather Prediction Center of the US National Oceanographic and Atmospheric Administration), for example, sees a continuing rapid growth in subscribers to its "Product Subscription Service" 7 that was initiated in 2005 and that exceeded 40,000 individual subscribers early in 2014. A survey of the subscribers to the SWPC service in 2013 enabled an assessment of the interests from the user side (Schrijver and Rabanal, 2013), which concluded that "[s]pace weather information is most commonly obtained for reasons of [indirect impacts through interruptions of power or communications on] human safety and continuity or reliability of operations. The information is primarily used for situational awareness, as aid to understand anomalies, to avoid impacts on current and near-future operations by implementing mitigating strategies, and to prepare for potential nearfuture impacts that might occur in conjunction with contingencies that include electric power outages or GPS perturbations.…”
Section: Space Weather: Society and Sciencementioning
confidence: 99%
See 2 more Smart Citations
“…The official US space-weather forecast center (the Space Weather Prediction Center of the US National Oceanographic and Atmospheric Administration), for example, sees a continuing rapid growth in subscribers to its "Product Subscription Service" 7 that was initiated in 2005 and that exceeded 40,000 individual subscribers early in 2014. A survey of the subscribers to the SWPC service in 2013 enabled an assessment of the interests from the user side (Schrijver and Rabanal, 2013), which concluded that "[s]pace weather information is most commonly obtained for reasons of [indirect impacts through interruptions of power or communications on] human safety and continuity or reliability of operations. The information is primarily used for situational awareness, as aid to understand anomalies, to avoid impacts on current and near-future operations by implementing mitigating strategies, and to prepare for potential nearfuture impacts that might occur in conjunction with contingencies that include electric power outages or GPS perturbations.…”
Section: Space Weather: Society and Sciencementioning
confidence: 99%
“…As with terrestrial weather, this means that the economic value of space weather forecasts likely significantly exceeds the total costs of detrimental impacts, and that this value would increase as forecast accuracy and specificity would increase. Other valuable uses of space weather information as indicated by the subscribers to space-weather information lie in anomaly analysis and system design specification (Schrijver and Rabanal, 2013).…”
Section: Space Weather: Society and Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Schrijver [] indicates that the economic benefits of mitigation could exceed the cost. However, there are various difficulties: Posner et al [] identified the inadequacy of existing solar monitoring instruments and the models for operational forecasting; the geophysical models of space weather and ground conductivity are not yet adequately integrated into GIC forecasting [ Lanzerotti , ]; the physical implementation of reducing GICs by installing neutral reactors and series capacitors is complex [ Arajärvi et al, ]; and most customers of space weather information lack the knowledge of how to respond to it [ Schrijver and Rabanal , ].…”
Section: Grid Vulnerabilitymentioning
confidence: 99%
“…However, there are potentially devastating problems at much lower levels of space environmental disturbances. A recent paper by Schrijver and Rabanal [23] shows that commercial users believe they could use space weather data to mitigate more routine, but nonetheless serious impacts to routine services such as GPS positioning and even commercial power.…”
Section: A Few Severe Satellite Anomalies and Their Probable Causesmentioning
confidence: 99%